Outcomes and Fate of the Distal Landing Zone Compared Between Prosthetic and Autologous Grafts After Infrainguinal Graft Occlusions - Rother, Ulrich; Gruber, Marc; Behrendt, Christian-Alexander; Günther, Josefine; Lang, Werner; Meyer, Alexander (JOURNAL OF VASCULAR SURGERY, 2022)
Background: Due to an increasing life expectancy, more and more patients experience the failure of peripheral arterial revascularization. This study aims to investigate patients treated for the failure of infra-inguinal bypass grafts, and to investigate the interaction of different bypass materials [great saphenous vein (GSV) and polytetrafluoroethylene (PTFE)] and the further outcome. Methods: Retrospective single-center analysis of consecutive patients treated for acute or chronic occlusion of infra-inguinal bypasses at a university hospital was conducted. Hospitalizations from 1st January 2010 through 31st December 2019 were included. Perioperative parameters from the index operation including graft material (prosthetic vs. autologous) were assessed. After bypass occlusion, the grade of ischemia, as well as the distal landing zone of the redo bypass compared with the primary bypass was investigated. Results: In this study, 158 (65% men and 35% women with a m mean age of 70.5 years) eligible patients were included (57% vein and 42% prosthetic bypass grafts). After graft occlusion, 47% of the patients presented with symptoms of acute limb-threatening ischemia, 53% with symptoms of chronic leg ischemia. The rate of acute limb-threatening ischemia was significantly higher when prosthetic graft material was used during the index operation (p =0.016). Additionally, in case of reoperation, the landing zone of the redo bypass was significantly more distally located after occlusion of prosthetic bypass graft (p = 0.014). Conclusion: Occlusions of prosthetic bypass grafts were associated with significantly higher rates of acute symptoms compared with vein grafts. Additionally, a shift to a more distal landing zone was recognized after the failure of a prosthetic bypass graft during the redo bypass operatio
CRIS-Team WoS Importer:2022-06-03
Keywords: graft failure; infrainguinal bypass; limb-threatening ischemia; prosthetic graft; vein bypass

Outcomes and Fate of the Distal Landing Zone Compared Between Prosthetic and Autologous Grafts After Infra-Inguinal Graft Occlusions - Rother, Ulrich; Gruber, Marc; Behrendt, Christian-Alexander; Günther, Josefine; Lang, Werner; Meyer, Alexander (Frontiers in Surgery, 2022)
Background: Due to an increasing life expectancy, more and more patients experience the failure of peripheral arterial revascularization. This study aims to investigate patients treated for the failure of infra-inguinal bypass grafts, and to investigate the interaction of different bypass materials [great saphenous vein (GSV) and polytetrafluoroethylene (PTFE)] and the further outcome. Methods: Retrospective single-center analysis of consecutive patients treated for acute or chronic occlusion of infra-inguinal bypasses at a university hospital was conducted. Hospitalizations from 1st January 2010 through 31st December 2019 were included. Perioperative parameters from the index operation including graft material (prosthetic vs. autologous) were assessed. After bypass occlusion, the grade of ischemia, as well as the distal landing zone of the redo bypass compared with the primary bypass was investigated. Results: In this study, 158 (65% men and 35% women with a m mean age of 70.5 years) eligible patients were included (57% vein and 42% prosthetic bypass grafts). After graft occlusion, 47% of the patients presented with symptoms of acute limb-threatening ischemia, 53% with symptoms of chronic leg ischemia. The rate of acute limb-threatening ischemia was significantly higher when prosthetic graft material was used during the index operation (p =0.016). Additionally, in case of reoperation, the landing zone of the redo bypass was significantly more distally located after occlusion of prosthetic bypass graft (p = 0.014) Conclusion: Occlusions of prosthetic bypass grafts were associated with significantly higher rates of acute symptoms compared with vein grafts. Additionally, a shift to a more distal landing zone was recognized after the failure of a prosthetic bypass graft during the redo bypass operation.
CRIS-Team Scopus Importer:2022-03-18
Keywords: graft failure; infrainguinal bypass; limb-threatening ischemia; prosthetic graft; vein bypass